The Gap Between Standards and Practices in Guidance and Counseling Management: A Systematic Analysis of the Implementation of Ministry of Education and Culture Regulation 111/2014 - Annisa Fitria Suherman; Muhammad Ridho Albari (Ma'soem University, 2026)
Ministry of Education and Culture Regulation No. 111 of 2014 establishes comprehensive standards for guidance and counseling services in schools, but implementation reports show a gap between regulations and practice. This study aims to analyze these gaps through a Systematic Literature Review using the PRISMA protocol. The search was conducted on Google Scholar, Portal Garuda, and institutional repositories for publications from 2014 to 2024. Of the 127 initial publications, 23 articles met the inclusion criteria and were analyzed using thematic synthesis and gap analysis. The results showed five main groups of gaps: counselor-student ratio (91%), counselor competence (78%), resource limitations across facilities, dual roles, and budget constraints (57–83%), lack of operational implementation standards and supervision (65%), and service quality with low to moderate client satisfaction (39%). The contributing factors were at the individual, school organization, system policy, and socio-geographical context levels. Overall, there were systemic and multidimensional implementation gaps, with the counselor-student ratio being the most consistent finding. Closing these gaps requires multi-layered interventions involving counselors, schools, and policymakers.